Greening the Smartness of Cities and Communities. - Dall’O’, Giuliano (Springer, 2020)
The topic of smart cities has come to the fore at a time when technological innovation in the cities, owing to the ever increasing use of ICT infrastructures and services, especially the Internet, is spreading widely. The digital city seems to have taken the upper hand over the real one, and cities are joining the smart revolution aiming to become smart cities. The risk is that the most concrete meanings of the smart revolution will be lost, giving too much weight to technologies. This chapter addresses this issue by highlighting the true meanings of the smart city approach on urban planning and the necessary and useful synergy with the green aspects most linked to the physical environment of the city.
Keywords: Smart City; Transformation; Digitalisierung; Informationstechnologie; Stadtökologie; Stadtumbau; Nachhaltige Stadtentwicklung